Validation of a water quality model for the Ria de Aveiro lagoon, Portugal - Lopes, J. F.
The main purpose of this work is to validate a water quality model for the Ria de Aveiro, in order to better use it as a predictive tool in the study of the main water quality processes in the lagoon. Ria de Aveiro is a very shallow lagoon, dominated by tidal currents, presenting a very complex network structure, composed by several sub-systems and dominated by tidal asymmetries, resulting in areas of ebb and flood dominance and weak gravitational circulation. Tidal currents are the main forcing in the dissolved oxygen distribution (DO). The DO concentrations inside the main areas of the lagoon remain quite high, around 8 mg O2/L, during great part of the year. The model sensitivity analysis shows that the ocean remains the main source of oxygen as well as the main factor controlling the DO distribution throughout the main lagoon areas, due to the exchanges between the ocean and the lagoon. This exchanges results from the good connection between them, which assure a tidal transport of oxygen and a constant renewal of the dissolved oxygen within the lagoon. As sea waters flows into the main lagoon channels, it increases, progressively, the oxygen concentration of the lagoon inner areas, to levels very comparable to the ocean level. This feature is responsible for the relatively high values of the DO concentrations found at the lagoon main areas, (varying within the range of 8 to 9 mg O2/L). The occurrence of some episodic hypoxia situation at the very far and shallow areas, namely during summer and neap tides, when the oxygen consumption related processes are dominant, is nevertheless possible. Indeed, at the intertidal areas and at areas situated at the far end of the lagoon, under the influence of weak tidal currents, the dissolved oxygen concentrations may become very low, if the phytoplankton concentration and metabolism are low. Furthermore, as the depth is reduced at those areas, if the air temperature increase, the DO lost to the atmosphere is enhanced. The sensitivity analysis shows, as well, that the primary production and the phytoplankton respiration are the main factors affecting the oxygen budget in the water column, where changes in the primary production, resulting from changes of the phytoplankton abundance or metabolism, may influence the oxygen concentrations in the water column. This study shows that the model is able to realistically simulate the water quality of the lagoon constituting, therefore, a tool for the study and management of the Ria de Aveiro ecosystem.